"We all need Purpose and Reason to be here.": A Qualitative Investigation of howmembers of Alcoholics Anonymous with Long-term Recovery Experience Aging. Issue 1 (2nd January 2022) - McInerney, Kevin; Garip, Gulcan; Benson, Tony
ABSTRACT: Using interpretative phenomenological analysis (IPA) and theoretically framed within Frankl's logotherapy, the current paper explored how members of Alcoholics Anonymous (AA) with long-term recovery (LTR) experience aging and health-related issues. Semi-structured interviews were undertaken to explore the lived experiences of three older members of AA with LTR. IPA revealed five higher-order group concepts: spirituality, being in the present, acceptance, self-esteemandfellowship: a support network. Interpretation of the themes revealed that LTR in AA is beneficial in helping individuals transition to later life, develop coping mechanisms for poor health and find a purpose and meaning to life.